1978
DOI: 10.1677/joe.0.0770157
|View full text |Cite
|
Sign up to set email alerts
|

Response of Antidiuretic Hormone to Acute Exposure to Mild and Severe Hypoxia in Man

Abstract: Eight men, 19-35 years of age, breathed 20.9% (normal oxygen), 13.9% (mild hypoxia) or 11.1% (severe hypoxia) oxygen in nitrogen gas mixtures during three 20 min periods, which were separated by 1 h recovery periods. The order in which the gas mixtures were breathed was random. The partial pressure of oxygen decreased from a mean of 93.5 during exposure to normal oxygen to 53.9 and 36.7 mmHg during mild and severe hypoxia respectively. There were corresponding decreases in haemoglobin saturation. The partial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…This response to exercise is consistent with other normoxic work, whereby exercise of [60% _ VO 2max is thought to induce renal hormone release through adrenocorticotrophic elevation (Viru 1992). However, hypoxia is thought to suppress ADH (Claybaugh et al 1978) and aldosterone (Bouissou et al 1987) release irrespective of exercise (Zaccaria et al 1998). Plasma osmolality did not significantly alter with exercise, even though it is widely thought plasma osmolality stimulates the release of renal hormones (Takamata et al 2000).…”
Section: Discussionsupporting
confidence: 87%
“…This response to exercise is consistent with other normoxic work, whereby exercise of [60% _ VO 2max is thought to induce renal hormone release through adrenocorticotrophic elevation (Viru 1992). However, hypoxia is thought to suppress ADH (Claybaugh et al 1978) and aldosterone (Bouissou et al 1987) release irrespective of exercise (Zaccaria et al 1998). Plasma osmolality did not significantly alter with exercise, even though it is widely thought plasma osmolality stimulates the release of renal hormones (Takamata et al 2000).…”
Section: Discussionsupporting
confidence: 87%
“…Such results appear to depend on whether direct estimates of vasopressin have been made rather than measurements of urine flow, the degree of hypoxia (Stickney, Northup & Van Liere, 1946;Subramanian, Bhatia & Siddiqui, 1975), whether conscious or anaesthetized animals were employed and the nature of the anaesthetic (Forsling, Ingram & Stanier, 1980). In general, hypoxia has little effect on vasopressin release in man (Baylis, Stockley & Heath, 1977;Forsling & Milledge, 1977: Claybaugh, Hansen & Wozniak, 1978), but appears to stimulate release in other animals (Share & Levy, 1966;Anderson, Pluss, Berns, Jackson, Arnold, Schrier & McDonald, 1978). In most studies anaesthetized animals and a relatively narrow range of oxygen tensions have been employed.…”
Section: Introductionmentioning
confidence: 99%
“…Renal water excretion is under the control of arginine vasopressin (AVP), and short-term hypoxia has generally resulted in no change in plasma AVP levels. 1,5,8 However, in two of these studies, some subjects had an increase in plasma AVP levels. 1,5 Only one study has reported the changes in plasma AVP levels during hypoxic exposure in which subjects experienced the spectrum of urine flow responses seen at altitude.…”
Section: Water: Role Of Arginine Vasopressinmentioning
confidence: 97%